The affinity, intrinsic activity and selectivity of a structurally novel EP2 receptor agonist at human prostanoid receptors. (4th January 2019) - Coleman, R A; Woodrooffe, A J; Clark, K L; Toris, C B; Fan, S; Wang, J W; Woodward, D F
Abstract : Background and Purpose: Prostanoid EP2 receptor agonists exhibit several activities including ocular hypotension, tocolysis and anti‐inflammatory activity. This report describes the affinity and selectivity of a structurally novel, non‐prostanoid EP2 receptor agonist, PGN‐9856, and its therapeutic potential. Experimental Approach: The pharmacology of a series of non‐prostanoid EP2 receptor agonists was determined according to functional and radioligand binding studies, mostly using human recombinant prostanoid receptor transfectants. The selectivity of PGN‐9856, as the preferred compound, was subsequently determined by using a diverse variety of non‐prostanoid target proteins. The therapeutic potential of PGN‐9856 was addressed by determining its activity in relevant primate cell, tissue and disease models. Key Results: PGN‐9856 was a selective and high affinity (pKi ≥ 8.3) ligand at human recombinant EP2 receptors. In addition to high affinity binding, it was a potent and full EP2 receptor agonist with a high level of selectivity at EP1, EP3, EP4, DP, FP, IP and TP receptors. In cells overexpressing human recombinant EP2 receptors, PGN‐9856 displayed a potency (pEC50 ≥ 8.5) and a maximal response (increase in cAMP) comparable to that of the endogenous agonist PGE2 . PGN‐9856 exhibited no appreciable affinity (up 10 μM) for a range of 53 other receptors, ion channels and enzymes. Finally, PGN‐9856 exhibited tocolytic, anti‐inflammatory and long‐acting ocular hypotensive properties consistent with its potent EP2 receptor agonist properties. Conclusions and Implications: PGN‐9856 is a potent, selective and efficacious prostanoid EP2 receptor agonist with diverse potential therapeutic applications: tocolytic, anti‐inflammatory and notably anti‐glaucoma.